Prevalence of atopy and asthma in overweight children and adolescents – a cross-sectional study - Wytrychowski, Krzysztof; Gałka, Agnieszka; Hans-Wytrychowska, Anna (Family Medicine & Primary Care Review, 2017)
Background . A steady growth in the prevalence of asthma and overweight in children has been observed over the last three decades. There is a lot of evidence that obesity in children is a risk factor in the development of asthma. Objectives . We examined the relationship between obesity and development of atopy and asthma in children aged 6–18. Material and methods . A cross-sectional study was performed based on the medical records of 175 children and adolescents treated at the allergology outpatient clinic with diagnosed atopic diseases. From the same age population of patients of the general medicine clinic, the medical records of 207 children and adolescents were randomly chosen as a control group. In study group, atopy was confirmed with the use of skin prick tests or the measurement of specific IgE antibodies. The weight, height and BMI were determined for all the studied children. Both groups were divided into subgroups of younger children (≤ 12 years) and adolescents (> 12 years). Results . In both groups, overweight children (BMI > 25; > 85th percentile) were identified. The groups were uniform as regards gender, age and BMI. The percentage of overweight children was greater in the group with atopy than in the control group (14.3% vs 5.3%; p = 0.043). In the groups ≤ 12 and > 12, the percentage of overweight and obese children was higher in the group with atopy than in the control group, but the difference was statistically insignificant (p = 0.142 and p = 0.061, respectively). In the group with atopy, the number of overweight children suffering from asthma was significantly smaller in the group of younger children than in the group of older children (7.4% vs 20.2%; p = 0.028). In the group with atopy, there were 148 children with correct body weight, out of which 2 children (1.3%) were diagnosed with asthma. 23 out of 25 overweight children (92%) were diagnosed with asthma (p < 0.001). Conclusions . In the studied population of children and adolescents with atopic diseases, the prevalence of overweight was greater compared with their healthy peers. Bronchial asthma is an atopic disease connected with a high prevalence of overweight and obesity in the studied subjects.